Readiness of Malaysian on Sustainable Development in Solar Energy Application - Khoo, Terh Jing; Chai , Tze Qing; Ha , Chin Yee (International Journal of Sustainable Construction Engineering and Technology, 2023)
Solar energy is a non-vanishing renewable source of energy that is eco-friendly. However, the solar energy adoption rate in Malaysia remains low due to the low readiness level among the Malaysian. This phenomenon should be emphasized where solutions need to be figured out to encourage the adoption of solar energy in buildings. Thus, this research was conducted to explore the readiness and challenges of the Malaysians in adopting solar energy. A mixed research method was adopted where a total of 200 sets of online questionnaire surveys were distributed to the public, and a semi-structured interview was carried out to obtain the opinions from the expert in the industry. Based on the findings of the questionnaires, the top 3 challenges in solar energy adoption are (1) high setting up cost of solar panels, (2) limited public awareness of solar energy and (3) efficiency of the solar panel depends on the weather. Next, the qualitative study found that 48.9% of 139 respondents were willing to adopt solar energy in the future. The findings show that that breaking down the barriers of high investment cost and long return investment would further enhance the solar energy adoption rates at the residential scale. Since this study had explored the challenges and solution to these barriers, the outcomes of this study can be used by the policy maker as the fundamental to encourage the adoption of solar energy in the existing buildings where the current adoption rate is low.